A novel ammonium pentaborate – poly(ethylene-glycol) templated polymer-inclusion compound. Issue 57 (27th June 2019) - Ploszajski, Anna R.; Billing, Matthew; Skipper, Neal T.; Cockcroft, Jeremy K.
Abstract : Reaction of ammonia borane with poly-ethylene glycol at slightly elevated temperatures leads to the formation of the first known example of a borate-based polymer inclusion compound with a pentaborate framework structure. Abstract : A new hydrogen-bonded supramolecular framework is reported, consisting of ammonium pentaborate, containing poly(ethylene-glycol) chains extending down tubular cavities in the structure. The crystal architecture is templated by the presence of the polyether chains, analogous to template synthesis of zeolites and metal organic frameworks. The ammonium pentaborate is formed by the thermolysis of ammonia borane, followed by hydrolysis of the dehydrogenation products by ambient water. This structure represents the first known example of a borate-based polymer inclusion compound.